Environmental Roman guardianship of forests-trees - Abelenda, Virginia (2011)
The consumer must also be clearly aware that today the purchase of reams of white paper implies the felling of trees, consequently, an attitude of "sustainable consumption" according to the preferred definition for the term proposed at the Oslo Symposium in 1994 and adopted by the third session of the United Nations Commission for Sustainable Development (CSD III) in 1995, where it was defined as: "The use of goods and services that respond to basic needs and provide a better quality of life, at the same time that minimize the use of natural resources, toxic materials, and emissions of waste and pollutants over the life cycle, in such a way that the needs of future generations are not jeopardized", a definition that is also connected with the most common internationally. of "sustainable development" which is used by the Brundtland Commission: "Sustainable development is that development that meets present needs without jeopardizing the ability of future generations to meet their own needs" (WCED, 1987:43), it would be, among others, the implementation of actions so that these destroyed trees are compulsorily replaced by others.